The impact of relational leadership on employee innovative work behavior in IT industry of China - Tayyaba Akram; Shen Lei; Muhammad Jamal Haider (Arab Economic and Business Journal, 2016)
This study is an attempt to investigate the effect of relational leadership (RL) on the three different stages of employee innovative work behavior (EIWB) in information technology industry of China. It also investigates the overall effect of relational leadership on total EIWB. It was proposed that relational leadership effects EWIB positively. For testing the hypotheses, a self-administered questionnaire was used to find out what are the responses of 261 employees from an IT company. Correlation and regression analysis suggested that relational leadership affects all three stages of employee innovative work behavior in significant manner. Its overall effect on EIWB is also very prominent in our analysis. The results of this study suggest that relational leadership, being a powerful motivational tool, helps employees to depict innovative work behavior at each of idea generation, idea promotion and idea realization stages of EIWB. The implications and limitations of the study are further discussed.
Keywords: 650; Relational leadership; Employee innovative work behavior; Idea generation; Idea promotion; Idea realization; China